Apakah Pemaafan Berkorelasi Dengan Psychological Well-Being Pada Remaja yang Tinggal Di Panti Asuhan? - Windi Astuti; Anggia Kargenti Evanurul Marettih (Universitas Andalas, 2018)
This study aimed to determine the corelation between forgiveness to psychological well-being in teenagers whose living in orphanages. Subject were obtained 172 adolescents who live in three orphanages in Pekanbaru by using purposive sampling technique that is 172. The Data were collected by using Psychological Well-being scale (Ryff) with reliability coefficient (0,885) and Thompson Heartland Forgiveness Scale (HFS) with reliability coefficient (0,839). The data analysis showed that there is a significant corelation between forgiveness and psychological well-being in teenagers whose living in the orphanages, with R= 0,790, and p = 0,000 (p≤0,05). When teenagers willing to forgive themselves, the situation and others people, it will make the teenagers able to establish a good relationships and able to give meaning for their experienced during life in orphanage which is corelate in perceiving psychological well-being. The low level of forgiveness is corelate with high psychological well-being. To improve the level of psychological well-being, teenegers must have to continue improving his or her own forgiveness, whether for forgiveness of self, others, or the situation.